Teologi Inklusif Master Cheng Yen dan Perannya di Yayasan Buddha Tzu Chi Indonesia - Prasuci, Tiara (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
Patriarchal understanding that differentiates social status and often demeans women are The patriarchal understanding that differentiates social status and often demeans women is challenged by the presence of Master Cheng Yen, a woman born on May 14, 1937 in Chingsui Village, Taichung County, Taiwan. Master Cheng Yen devoted herself as a nun and succeeded in establishing a Social Assistance Foundation called the Tzu Chi Buddhist Foundation which was first established in Qingshui, Taichung, Taichung, central Taiwan, in 1966. Theology Master Cheng Yen's inclusive theology is the nature of compassion which he teaches to be the basis for doing all kinds of good and helping others. basis for doing all kinds of good and helping anyone regardless of social status, race, culture, or religion. social status, race, culture, religion, ethnicity. And this Buddha Tzu Chi Foundationhas 4 (four) main missions, namely Education Mission, Health Mission, Charity Mission, and Humanist Culture Mission and this foundation has spread in various regions. This foundation has spread to various remote areas in various countries, one of which is in Indonesia, precisely in the Pantai Indah Kapuk BGM area, North Jakarta.